Incidencia del uso de la plataforma de aprendizaje virtual Dokeos en el proceso enseñanza aprendizaje del 7mo, 8vo, 9no y 10mo grado de educación general básica de la unidad educativa particular bilingüe Alexander de la ciudad de Machala. Periodo Lectivo 2014-2015. - Galarza Fernández, Julio Humberto (2015)
Technology and its overwhelming advance has allowed imbedded in all loso fields of science, so now also provides many benefits to education, specifically to the development of the teaching-learning process, taking it very clear that for incorporation must implement strategies and suitable techniques, for only thus can benefit from the support provided to us.